Rare Diseases Leading to Childhood Glaucoma: Epidemiology, Pathophysiogenesis, and Management. (16th September 2015) - Abdolrahimzadeh, Solmaz; Fameli, Valeria; Mollo, Roberto; Contestabile, Maria Teresa; Perdicchi, Andrea; Recupero, Santi Maria
Abstract : Noteworthy heterogeneity exists in the rare diseases associated with childhood glaucoma. Primary congenital glaucoma is mostly sporadic; however, 10% to 40% of cases are familial. CYP1B1 gene mutations seem to account for 87% of familial cases and 27% of sporadic cases. Childhood glaucoma is classified in primary and secondary congenital glaucoma, further divided as glaucoma arising in dysgenesis associated with neural crest anomalies, phakomatoses, metabolic disorders, mitotic diseases, congenital disorders, and acquired conditions. Neural crest alterations lead to the wide spectrum of iridocorneal trabeculodysgenesis. Systemic diseases associated with childhood glaucoma include the heterogenous group of phakomatoses where glaucoma is frequently encountered in the Sturge-Weber syndrome and its variants, in phakomatosis pigmentovascularis associated with oculodermal melanocytosis, and more rarely in neurofibromatosis type 1. Childhood glaucoma is also described in systemic disorders of mitotic and metabolic activity. Acquired secondary glaucoma has been associated with uveitis, trauma, drugs, and neoplastic diseases. A database research revealed reports of childhood glaucoma in rare diseases, which do not include glaucoma in their manifestation. These are otopalatodigital syndrome, complete androgen insensitivity, pseudotrisomy 13, Brachmann-de Lange syndrome, acrofrontofacionasal dysostosis, caudal regression syndrome, and Wolf-Hirschhorn syndrome.